Human COQ4 deficiency: delineating the clinical, metabolic and neuroimaging phenotypes. Issue 9 (16th October 2021) - Laugwitz, Lucia; Seibt, Annette; Herebian, Diran; Peralta, Susana; Kienzle, Imke; Buchert, Rebecca; Falb, Ruth; Gauck, Darja; Müller, Amelie; Grimmel, Mona; Beck-Woedel, Stefanie; Kern, Jan; et al.
Abstract : Background: Human coenzyme Q4 (COQ4) is essential for coenzyme Q10 (CoQ10 ) biosynthesis. Pathogenic variants in COQ4 cause childhood-onset neurodegeneration. We aimed to delineate the clinical spectrum and the cellular consequences of COQ4 deficiency. Methods: Clinical course and neuroradiological findings in a large cohort of paediatric patients with COQ4 deficiency were analysed. Functional studies in patient-derived cell lines were performed. Results: We characterised 44 individuals from 36 families with COQ4 deficiency (16 newly described). A total of 23 different variants were identified, including four novel variants in COQ4 . Correlation analyses of clinical and neuroimaging findings revealed three disease patterns: type 1: early-onset phenotype with neonatal brain anomalies and epileptic encephalopathy; type 2: intermediate phenotype with distinct stroke-like lesions; and type 3: moderate phenotype with non-specific brain pathology and a stable disease course. The functional relevance of COQ4 variants was supported by in vitro studies using patient-derived fibroblast lines. Experiments revealed significantly decreased COQ4 protein levels, reduced levels of cellular CoQ10 and elevated levels of the metabolic intermediate 6-demethoxyubiquinone. Conclusion: Our study describes the heterogeneous clinical presentation of COQ4 deficiency and identifies phenotypic subtypes. Cell-based studies support the pathogenic characteristics of COQ4 variants. Due to the insufficient clinical response to oral CoQ10 supplementation, alternative treatment strategies are warranted.